The extent of NRT's commitment to the instructions of the Election Commission: "Kurdistan Region Elections 2024 as a model - Amin, Asst.L.Shana Ahmad Amin; Hussein, Asst.Prof.DR.Yohan Osman Hama Hussein Hama; Taha, Asst.L.Kosrat Taha (Sulaimani Journal for Humanities, 2025)
This study attempts to assess the level of compliance of NRT media with the guidelines of the Independent Election Commission of Iraq, during the campaign for the sixth session of the Kurdistan Parliament in 2024. Descriptive and methodological methods of content analysis and formal analysis tools are used. (263) media articles on NRT channel and (18) media articles on NRT website were randomly processed. During the 25 days of the election campaign from (25/9/2024 to 20/10/2024) as research samples were identified and analyzed. The aim of the study is to: - To determine the extent of importance of NRT media to the parties that speak the language, with the extent of compliance with the same media to the laws and guidelines of the Commission. The most important conclusions reached by the study are: 1. NRT channels and websites have tried to convince voters to participate and vote for Nawa-i-Nuw through the use of effective phrases that were the language of the party during the 2024 election campaign. 2. NRT has tried to comply with the laws and guidelines of the Commission during the election campaign, although they have violated the laws and guidelines in some cases.
Keywords: Department of Media; Faculty of Humanities; Sulaimani University; Kurdistan Region; Iraq